Does CEO power affect audit's report lag in the Gulf Cooperation Council (GCC) economies? The curtailing role of corporate governance - Saidin, Saidatunur Fauzi; Abdul Hamid, Mohamad Ali; Khan, Faisal (Inderscience Enterprises, 2023)
This study provides empirical evidence on how the chief executive officer (CEO) power influences audit report lag (ARL) for non-financial firms of GCC economies from 2009 to 2018. The ordinary least squares (OLS) regression is used in our analyses to test our hypotheses. Results show that CEO-tenure and duality increase ARL in GCC economies. Additional, we find that the effect of CEO-tenure on ARL is curtailed when board independence is stronger, whereas the effect of CEO duality is unchanged by board independence. Further, the impact of CEO power on ARL remains unchanged when there is a gender-diverse board. However, gender diversity curtails the positive impact of CEO power (CEO-tenure and CEO duality) on ARL only when female representation is two or more on the corporate board. In brief, our study identifies CEO power and corporate governance as previously unrecognised determinants of ARL in GCC economies.